Iowa spring bird report contributed by Babs Padelford and Loren Padelford, spring 1996 - Padelford, Babset al; Padelford, Lorenet al (1996)
Spring report of birds found in western Iowa contributed by Babs Padelford and Loren Padelford. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1996. Epson - sheet feed